[2] [N,N,N ,N -tetraalquilsuccinamida] rotaxa [1,7,14,20-tetraaza-2,6,15,19-tetraoxo-3,5,9,12,16,18,22,25-tetrabenzocicloexacosano]: síntese e estrutura - Rodrigues, Letícia Valvassori (2013)
This work presents the synthesis of five new planned [2]rotaxanes whith thread derivates succinamide [R1R2NC(O)CH2CH2C(O)NR1R2, where R1 = R2 = Pr, i-Pr, Bu, i-Bu e R1 = CH2Cy e R2 = CH2Ph]. The compounds were obtained by a five-component clipping reaction. Several studies have been conducted with these compounds such as: deslipping reactions, structural analysis, molecular dynamics by using solution 1H NMR spectroscopy and intra and intermolecular interactions using Hirshfeld surface. From these results, it was observed that the deslipping reaction was highly effective when microwave irradiation was employed and the reaction has shown to be an efficient model for the synthesis of macrocycles. Moreover, it was possible to calculate the rotational energy barrier of the macrocycle around the thread of [2]rotaxanes. In addition, when the Hirshfeld surface was used, it was possible to demonstrate all of the non-covalent interactions between the submolecular components as well as the intermolecular interactions of [2]rotaxane.